HUBUNGAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR FISIKA DI SMA N 3 MUARO JAMBI - Yolviansyah, Fauziah; Suryanti, Suryanti; Rini, Endah Febri Setiya; Wahyuni, Sri; Matondang, Maria Marisa (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2021)
This study ams to determine the relationship between interst in learning physics and student leraning outcomes. This research uses a quantutative research type, with the research instrument using a questionnaire. The focus of this research is on 4 dimensions, namely the adoption of a scientific attitude, the pleasure of learning physics, and an interest in learning physics. The sample of this research was students of class XII MIA with a total of 60 students. This research was conducted at SMA N 3 MUARO JAMBI. Then, the data were analyzed using the SPSS 24 program to determine whether the data was normal, and using the Kolmogorov-Smirnov correlation test to see whether each variable had a relationship with one another. Based on research and test results from the Kolmogorov-Smirnov correlation test, a significance value of 0,000 was obtained. This means that the significance value of 0.000